Influence of Drilling Methods on the Results of Standard Penetration Test in Loess–Paleosol Sequence - Li, Xin; Li, Yanrong; Lv, Dongdong; He, Shengdi; Zhang, Weiwei (Frontiers in Built Environment, 2022)
Standard penetration test (SPT) is an important in-situ measurement for field investigation of geotechnical and geological engineering. The drilling approaches for implementation of SPT can be classified into dry, wet and water circulation drillings according to the amount of water used during drilling process. However, the influences of these drilling methods on the SPT results remain unclear, especially when being used in loess–paleosol sequence which is water sensitive. In this study, SPT tests were conducted in a typical loess strata in the Loess Plateau of China. The difference of SPT N values under the above three drilling methods were compared together with the analysis of characteristics of samples from SPT sampler. The results showed that the N value exhibits positive correlation with dry density of the soil and negative correlation with water content. In shallow soil, the average N value under water circulation drilling was slightly higher than that of dry and wet drilling. This is because that the residual soil at the bottom of the drillhole caused by water circulation drilling provides additional penetration resistance. In deep soil, the difference of average N values among all three drilling methods was minimal although the structure of the samples from the SPT sampler differs from one another, indicating the determination of soil density on the SPT result. Empirical equations were proposed for the estimation of unconfined compressive strength of loess–paleosol sequence on the basis of SPT N values under the three drilling methods. Considering the efficiency of drilling and stability of SPT results, it is suggested that wet drilling is the most applicable method for implementation of SPT in the field investigation of loess–paleosol sequence.